ANALISIS DAMPAK MEDIA SOSIAL DI KOTA BANDUNG SEBAGAI KOTA PILIHAN UNTUK BERWISATA - Permana, Agam Julian; Ginting, Ayu Rahayu Muliani; Putri, Nathaya Rasendriya; Zharifa, Shania Siti Nur; Novita, Syalwa; Permana, Zahira Rafeyfa (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2024)
The tourism sector in Bandung City continues to increase in terms of the development of tourist objects that are increasingly varied and have an impact on other sectors such as the economy, society, and environment. The Ministry of Tourism and Creative Economy of the Republic of Indonesia stated that Bandung was ranked 15th out of 25 cities in the world with the category